Composition Medium Comparability in a Direct Writing Assessment of Non-Native English Speakers - Edward W. Wolfe; Jonathan R. Manalo (Language Learning and Technology)
The Test of English as a Foreign Language (TOEFL) contains a direct writing assessment, and examinees are given the option of composing their responses at a computer terminal using a keyboard or composing their responses in handwriting. This study sought to determine whether performance on a direct writing assessment is comparable for examinees when given the choice to compose essays in handwriting versus word processing. We examined this relationship controlling for English language proficiency and several demographic characteristics of examinees using linear models. We found a weak two-way interaction between composition medium and English language proficiency with examinees with weaker English language scores performing better on handwritten essays while examinees with better English language scores performing comparably on the two testing media. We also observed predictable differences associated with geographic region, native language, gender, and age.